2009
DOI: 10.1073/pnas.0904833106
|View full text |Cite
|
Sign up to set email alerts
|

Centromere repositioning in cucurbit species: Implication of the genomic impact from centromere activation and inactivation

Abstract: The centromere of an eukaryotic chromosome can move to a new position during evolution, which may result in a major alteration of the chromosome morphology and karyotype. This centromere repositioning phenomenon has been extensively documented in mammalian species and was implicated to play an important role in mammalian genome evolution. Here we report a centromere repositioning event in plant species. Comparative fluorescence in situ hybridization mapping using common sets of fosmid clones between two pairs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 41 publications
5
87
0
Order By: Relevance
“…Because previous inferences of fission as a dominant mechanism of structural evolution within a particular lineage have generally been made on the basis of relationships between genome size and chromosome number, they often could not reconstruct individual evolutionary events (but see Han et al, 2009). Our results for Mimulus suggest that wholesale chromosomal fission may be important even in taxa without incremental series of chromosome numbers, and provide an opportunity to investigate its mechanisms and consequences for plant evolution.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Because previous inferences of fission as a dominant mechanism of structural evolution within a particular lineage have generally been made on the basis of relationships between genome size and chromosome number, they often could not reconstruct individual evolutionary events (but see Han et al, 2009). Our results for Mimulus suggest that wholesale chromosomal fission may be important even in taxa without incremental series of chromosome numbers, and provide an opportunity to investigate its mechanisms and consequences for plant evolution.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, chromosome breakage can lead to the recruitment of kinetochore proteins to new DNA sequences/locations and the epigenetic creation of functional neocentromeres (Topp et al, 2009;Fu et al, 2013). Such centromere repositioning events, accompanied by a shift in the centromere-associated tandem DNA repeat, appear to have been important in chromosome number evolution within the cucurbits (Han et al, 2009). Nonetheless, polyploidy has been concluded to be the major source of chromosome number increases in plants (Jones, 1998), except in a few odd lineages such as Zamia (Olson and Gorelick, 2011), slipper orchids (Cox et al, 1998) and sedges (Chung et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The centromere repositioning during karyotype evolution, the so-called evolutionary new centromere (ENC) formation, is rather a common phenomenon. It has been repeatedly described in different taxonomic groups as diverged as mammals, birds, and plants (Kasai et al 2003;Nagaki et al 2004;O'Neill et al 2004;Galkina et al 2006;Han et al 2009;Skinner et al 2009;Rocchi et al 2012). Though mechanisms of ENC formation are obscure, an attractive hypothesis implies the following events: old centromere inactivation and neocentromere formation in a new euchromatic locus, with fixation of these first steps in population.…”
Section: Discussionmentioning
confidence: 99%
“…Recent comparative genetic analysis clearly showed that the five of the cucumber's seven chromosomes arose from fusions of ten ancestral chromosomes after divergence from C. melo ). Comparative fluorescence in situ hybridization (FISH) mapping using the same sets of fosmid clones revealed different centromeric positions between two pairs of chromosomes from these two species (Han et al 2009). Thus, chromosomal fusion and centromere repositioning occurred during the evolution of cucumber and melon chromosomes.…”
Section: Introductionmentioning
confidence: 99%